Analysis of Cases of Theft of Product Packaging Trademark Names of PT. Sinde Budi Sentosa Against Wen Ken Drug Co (PTE) LTD - Cindy Alisia Sinaga (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
This article reviews the dispute over the Brand Cap Rhino and Cap Kaki Tiga. The background to this incident is the dispute over the Brand, between Budi Yuwono, from PT. Sinde Budi Sentosa, the owner of the Cap Badak Brand, and Wen Ken Drug Co., Pte Ltd, the owner of the Cap Kaki Tiga product, which had the initial Brand of the Cap Kaki Tiga refreshing solution. The dispute arose because of a lawsuit from Wen Ken Drug because Cap Rhino imitated Cap Kaki Tiga. The Cap Kaki Tiga brand was won by the Commercial Court and Budi Yuwono made an appeal to the Supreme Court and in the Supreme Court decision, Budi Yuwono won over Wen Ken Drug. (Pte) Ltd.